2005
DOI: 10.1007/s00254-005-1285-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temporal and spatial variability of soil salinity in a coastal saline field

Abstract: The online version of the original article can be found at http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Many studies have demonstrated heterogeneity for soils in coastal field and spatial-temporal variation among soil sections due to climate, ground-water levels, and vegetation (Shi et al, 2005;Cemek et al, 2007). The establishment of vegetation on coastal saline field resulted in the significant spatial variability of soil physicochemical and microbiological properties when they adapt themselves to soil environment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated heterogeneity for soils in coastal field and spatial-temporal variation among soil sections due to climate, ground-water levels, and vegetation (Shi et al, 2005;Cemek et al, 2007). The establishment of vegetation on coastal saline field resulted in the significant spatial variability of soil physicochemical and microbiological properties when they adapt themselves to soil environment.…”
Section: Discussionmentioning
confidence: 99%
“…The nugget values of groundwater TDS and depth indicated there were experimental error and variation induced by smaller sampling scales. Percentages were used to denote the nugget/sill ratio, which is the standard way of classifying the spatial dependence of regional variables (Chien, Lee, Guo, & Houng, ; Shi, Li, Wang, & Makeschine, ). Table shows that the nugget/sill ratios of groundwater TDS and depth were both lower than 25%, indicating that the two had relatively strong spatial dependence.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution map intuitively reflected the spatial distribution of soil conductivity, which was helpful for reinforcing land management plans. The subjectivity of choosing agricultural production practices can be reduced by analyzing experimental data and evaluating the results with the reference values (Shi et al, ). As shown in Figure , in the study area, soil conductivity was higher in the northwestern and the northern parts (highest in the red region).…”
Section: Resultsmentioning
confidence: 99%
“…In performing 3D-IDW interpolation, the Z axis was enlarged by 300 times, and the number of search points was set to 6 [35], and then the map of spatio-temporal distribution of soil conductivity was obtained (Figure 3). Figure 3 intuitively revealed spatio-temporal variation of soil salinity in 3D and the simple visual observation could provide valuable information on the status of soil salinity [36] and development of management practices such as irrigation in cotton field. Following the grading standard of soil salinization defined by the American Salinity Laboratory [30], the soil ECe in this study was divided into five levels: non-saline soil (0~2 dS m −1 ), mildly saline soil (2~4 dS m −1 ), moderately saline soil (4~8 dS m −1 ), heavily saline soil (8~16 dS m −1 ), saline soil (>16 dS m −1 ).…”
Section: Spatio-temporal Of Distribution Of Soil Electrical Conductivmentioning
confidence: 97%